1996
DOI: 10.1111/j.1749-7345.1996.tb00594.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Substituting Selected Oilseed Protein Concentrates for Fish Meal in Rainbow Trout Oncorhynchus mykiss Diets

Abstract: Three oilseed protein concentrates (soybean, canola, and sunflower) were evaluated to determine their potential, when supplemented with deficient essential amino acids, to partially or completely replace fish meal in diets fed to rainbow trout Oncorhynchus mykiss. Triplicate aquaria of juvenile trout (average weight of 12 g) were fed the experimental diets for 10 wk, at which time the average weight of the fish was approximately sixfold higher than the initial weight. Average fish weight gains on diets in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 8 publications
6
51
0
Order By: Relevance
“…Hossain and Jauncey (1989) found that Bangladeshi variety of sesame oilseed meal can be included up to 25% in raw condition in the diet of Cyprinus carpio L. Hossain et al (1992) substituted fish meal with sesame oilseed meal in the diets of catfish, Heteropneustes fossilis and reported promising result. Similarly, Stickney et al (1996) found that sunflower protein concentrate can replace 25% fish meal protein in rainbow trout diets. Sanz et al (1994) observed better results when replacing 40% of the animal protein in rainbow trout with sunflower protein supplemented with Essential Amino Acids.…”
Section: Discussionmentioning
confidence: 92%
“…Hossain and Jauncey (1989) found that Bangladeshi variety of sesame oilseed meal can be included up to 25% in raw condition in the diet of Cyprinus carpio L. Hossain et al (1992) substituted fish meal with sesame oilseed meal in the diets of catfish, Heteropneustes fossilis and reported promising result. Similarly, Stickney et al (1996) found that sunflower protein concentrate can replace 25% fish meal protein in rainbow trout diets. Sanz et al (1994) observed better results when replacing 40% of the animal protein in rainbow trout with sunflower protein supplemented with Essential Amino Acids.…”
Section: Discussionmentioning
confidence: 92%
“…Decreased palatability, which in turn could lead to decreased consumption, is also a concern when fishmeal is replaced by plant-derived ingredients Stickney et al 1996).…”
Section: Complexities Posed By Developing Plant-based Dietsmentioning
confidence: 99%
“…In addition, plant meals may contain anti-nutritional factors such as trypsin inhibitors, non-digestible carbohydrates, lectins, saponins, phytates, and, possibly-allergenic storage proteins (Salunkhe et al 1992). Replacement of fishmeal by plant meal may decrease palatability (Geurden et al 2005), which in turn could decrease consumption Stickney et al 1996). In addition, chemical composition of fillets and organoleptic characteristics of fish fed with plant diets differ from those of fish fed traditional diets (Francesco et al 2004).…”
Section: Evaluation Of Family Growth Response To Fishmeal-and Plant-bmentioning
confidence: 99%
“…In search of fish meal alternatives in aqua feeds, rapeseed (including canola) products have been widely tested as protein sources in diets for several fish species, among them rainbow trout Oncorhynchus mykiss (Stickney et al 1996;Burel et al 2001;Thiessen et al 2003Thiessen et al , 2004Shafaeipour et al 2008), tilapia Oreochromis niloticus (Davies et al 1990), wels catfish Silurus glanis (Slawski et al 2011b) and turbot Psetta maxima (Burel et al 2000a, c).…”
Section: Introductionmentioning
confidence: 99%